Analisis Kreativitas Produksi Terhadap Kesuksesan Usaha Kecil Menengah (UKM)Klanting (Desa Tahai Baru Pangkuh 4) - Lili Sumiati; Uda, Tonich; Alexandro, Rinto (FKIP, Universitas Palangka Raya, 2023)
The improvement in the quality and creativity of workers, which is reflected by the better average level of education, has a positive impact on work productivity. Likewise, efforts to increase skills and training of workers accompanied by the application of appropriate technology have an impact on increasing work productivity. Every business or business wants to get business success, a business is said to be successful if it makes a profit, even though profit is not the only aspect that is assessed from the success of a business, but the reason profit is an important factor is because profit is the goal of people doing business. If there is a decline or instability in profits, the business will find it difficult to operate its business activities and maintain its business resilience. The purpose of this study is to describe Production Creativity to the Success of Small and Medium Enterprises (UKM) in Klanting in Tahai Baru Pangkung 4 Village, Maliku District, Pulang Pisau Regency. This type of research is qualitative research. This research involves 4 (four) informants. The data taken in this study is to make observations first, then conduct interviews, and document the data needed, then analyzed qualitatively including data reduction, presenting data, and drawing conclusions. The results showed that: Small and Medium Enterprises (UKM) Klanting did production based on the creativity of the owner of the clanting business. The clanting business has creativity and products that taste good and are free from harmful ingredients such as formalin and borax. In promoting the information conveyed in accordance with the condition of the product being sold. Small and Medium Enterprises (UKM) Klanting has two different flavors with the same form, namely original and non-original clanting